AKI in the elderly: A literature Review (Journal of Bangladesh College of Physicians and Surgeons, 2025)
Acute Kidney Injury (AKI) is a prevalent concern in the elderly population due to age-related changes in kidney structure and function, compounded by the increased prevalence of comorbid conditions. As the global population of individuals aged over 65 rises, understanding the mechanisms, risk factors, and outcomes associated with AKI in this demographic becomes imperative. The aging process leads to significant renal alterations, including a reduction in renal mass, loss of nephrons, and a decline in glomerular filtration rate (GFR), which greatly diminishes kidney function and resilience to injury.Elderly individuals often present with multiple comorbidities such as hypertension, diabetes, and heart failure, increasing their risk for AKI. The incidence of AKI in older adults has been steadily rising, influenced by factors like insufficient hydration, nephrotoxic medication use, and surgical procedures. Moreover, AKI is frequently under-diagnosed and mismanaged in this age group, leading to inadequate treatment and poorer health outcomes. Patients with AKI experience not only a higher short- and long-term mortality risk but also diminished quality of life and increased likelihood of progressing to chronic kidney disease (CKD) or end-stage renal disease (ESRD). Education on prevention strategies—including promoting hydration, avoiding nephrotoxic agents, and proper medication management—is crucial. Given the complexities of AKI in the elderly, a tailored approach focusing on early detection, preventive measures, and supportive care is essential for improving outcomes in this vulnerable population.J Bangladesh Coll Phys Surg 2025; 43: 154-172